Clinical Management of Hypoplastic Amelogenesis Imperfecta in Pediatric Patients: A Case Report and Review of Literature - Kamareh , Sanaz; Ansari, Ghassem; Soleymani , Ali Asghar; Roodgarian, Romina; Yadegari , Atiye (Journal of Dental School, 2021)
Objectives Amelogenesis imperfecta (AI) refers to a group of hereditary disorders that affect the quality and/or quantity of dental enamel of both primary and permanent dentitions. Also, these patients may suffer from certain systemic disorders and other dental and skeletal defects or abnormalities. Case: A 9-year-old female patient with hypoplastic type AI with unerupted maxillary first molars, and pulpal calcifications is reported. Her permanent anterior teeth were restored with composite veneer while the posterior teeth received stainless steel crowns. Conclusion Hypoplastic type AI is a rather uncommon disorder. Early treatment of AI, not only prevents tooth wear, but also has a positive psychological impact on children. The possible association of AI with nephrocalcinosis can also be monitored through initial radiographic evidence of pulp stones.